2015
DOI: 10.1002/jcp.25089
|View full text |Cite
|
Sign up to set email alerts
|

S‐Adenosylmethionine Affects ERK1/2 and Stat3 Pathways and Induces Apotosis in Osteosarcoma Cells

Abstract: Osteosarcoma is a very aggressive bone tumor. Its clinical outcome remains discouraging despite intensive surgery, radiotherapy, and chemotherapy. Thus, novel therapeutic approaches are demanded. S-Adenosylmethionine (AdoMet) is a naturally occurring molecule that is synthesized in our body by methionine adenosyltransferase isoenzymes and is also available as a nutritional supplement. AdoMet is the principal methyl donor in numerous methylation reactions and is involved in many biological functions. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 75 publications
3
43
0
Order By: Relevance
“…In our experimental model, AdoMet induced cell cycle arrest at the G 2 /M transition by down‐regulating the expression of cyclin B and by increasing the expression of p53 and cell cycle‐inhibitors p21 and p27. Interestingly we have recently demonstrated that AdoMet induced cell‐cycle arrest at G 2 /M phase and activation of apoptosis in U2OS osteosarcoma cells (Ilisso et al, ). Moreover, our research group has also reported that AdoMet potentiates the antitumor effect of doxorubicin by inducing the extrinsic pathway of apoptosis through the activation of the death receptor FAS in breast cancer cell line CG5 (Ilisso et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our experimental model, AdoMet induced cell cycle arrest at the G 2 /M transition by down‐regulating the expression of cyclin B and by increasing the expression of p53 and cell cycle‐inhibitors p21 and p27. Interestingly we have recently demonstrated that AdoMet induced cell‐cycle arrest at G 2 /M phase and activation of apoptosis in U2OS osteosarcoma cells (Ilisso et al, ). Moreover, our research group has also reported that AdoMet potentiates the antitumor effect of doxorubicin by inducing the extrinsic pathway of apoptosis through the activation of the death receptor FAS in breast cancer cell line CG5 (Ilisso et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because of its peculiar biological and pharmacological properties, AdoMet is an approved nutritional supplement. Recent in vitro and in vivo studies highlighted the effects of AdoMet on cancer progression by regulating key cellular processes, such as proliferation, differentiation, cell cycle, and apoptosis (Ilisso et al, ; Li et al, ; Lu & Mato, , ; Luo et al, ; Martínez‐López et al, ; Parashar et al, ; Pakneshan et al, ). The interest on AdoMet was recently focused on its epigenetic regulating activity of genes involved in the regulation of cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S-adenosylmethionine (SAMe) is an essential compound in many metabolic pathways, serving as a methyl donor and a precursor for polyamines and glutathione (GSH) [10]. Most patients with liver injury or a chronic liver disease, like cirrhosis, have impaired SAMe biosynthesis due to reduced MAT1A expression and MAT I/III inactivation, which are respectively the enzyme and isoenzyme involved in SAMe synthesis in normal hepatocytes [11, 12].…”
Section: Introductionmentioning
confidence: 99%